Phenological Phases and Thermal Mode of the Winter Wheat in the Irrigated Areas in the Fergana Region (International Journal of Psychosocial Rehabilitation, 2020)
This article investigates the average seasonal temperatures and precipitation values for the Fergana region based on meteorological and agrometeorological observations at meteorological stations in the Fergana region. Changes in thermal regimes and temperatures and precipitation required for the development of the phenological phases of winter wheat were studied in the region. The phenological phases of winter wheat cultivated in the region are analyzed depending on the thermal regime. Given the meteorological conditions, the optimal timing of winter wheat sowing is recommended.